CGIAR Initiative on One Health: Ethiopia stakeholder workshop, 26 April 2023 - Lore, Tezira A. (2023)
On 26 April 2023, the CGIAR Initiative on One Health held a stakeholder workshop at the Addis Ababa campus of the International Livestock Research Institute, with some participants joining online via Microsoft Teams. The objective of the workshop was to review the progress of the initiative’s research in the target countries, with a focus on the work in Ethiopia, and explore how the initiative can better support One Health activities in Ethiopia and the region at large.